Victory without violence : the first ten years of the St. Louis Committee of Racial Equality (CORE), 1947-1957 - Kimbrough, Mary (University of Missouri Press, 2000)
"Victory without Violence is the story of a small, integrated group of St. Louisans who carried out sustained campaigns from 1947 to 1957 that were among the earliest in the nation to end racial segregation in public accommodations. Guided by Gandhian principles of nonviolent direct action, the St. Louis Committee of Racial Equality (CORE) conducted negotiations, demonstrations, and sit-ins to secure full rights for the African American residents of St. Louis." "The book opens with an overview of post-World War II racial injustice in the United States and in St. Louis. After recounting the genesis of St. Louis CORE, the writers vividly depict activities at lunch counters, cafeterias, and restaurants and relate CORE's remarkable success in winning over initially hostile owners, managers, and service employees. A detailed review of its sixteen-month campaign at a major St. Louis department store, Stix Baer & Fuller, illustrates the group's patient persistence. With the passage of a public accommodations ordinance in 1961, CORE's goal of equal access was finally realized throughout the city of St. Louis." "On-the-scene reports drawn from CORE newsletters (1951-1955) and reminiscences by members appear throughout the text. In a closing chapter, the authors trace the lasting effects of the CORE experience on the lives of its members. Victory without Violence casts light on a previously obscured decade in St. Louis civil rights history."--Jacket.